Phytochemical, acute toxicity and renal protective appraisal of Ajuga parviflora hydromethanolic leaf extract against CCl4 induced renal injury in rats - Samiullah Burki; Zeba Gul Burki; Muhammad Arif Asghar; Imdad Ali; Saba Zafar (BMC, 2021)
Abstract Background Degenerative kidney diseases are mostly associated with oxidative stress. Natural products are considered as the antioxidants enrich food that can restrict the progress of oxidative stress induced disorders. Therefore, the present study was aimed to evaluate the renal protective effect of Ajuga parviflora leaf extract in carbon tetrachloride intoxicated rats. Methods The hydromethanolic extract of A. parviflora leaves was obtained by extracting twice in 60% methanol. The principal bioactive constituents were detected by LC/MS analysis. Toxicity of plant extract was assessed using brine shrimp lethal toxicity test and acute toxicity model on healthy Sprague-Dawley male rats. Nephroprotective effects of plant extract were also evaluated on rats by inducing CCl4 renal toxicity in comparison with positive control and naïve groups. The dose of A. parviflora administered to animal was 100, 200 and 300 mg/kg. All administrations were given orally on an alternate day basis for 30 days. Urine and serum biomarkers were analyzed, along with antioxidant enzymes. Finally, the DNA damages, lipid peroxides, hydrogen peroxides and nitrites were assessed in rat's renal tissue. The histopathology alterations in renal tissues were further studied for kidney damages. Results The LC/MS analysis confirmed the presence of different important pharmacological compounds in A. parviflora methanolic leaf extract. The key bioactive compounds include pyocyanin, zonisamide, D Saccharic acid, altretamine, carbocyclic thromboxane A2, Sinapyl alcohol, and vitamin C. The important polypeptides identified include Lys-Tyr-Lys, His-His-Lys, Met-Asp-Arg, Phe-Val-Arg, and PyroGlu-Val-Arg. The LD50 of A. parviflora was found to be > 1000 μg/mL. A. parviflora administration significantly subsides CCl4 toxicity in rats, reduced the elevated level of RBCs, pus and epithelial cells. The abnormal elevated level of specific gravity, creatinine, urobilinogen, urea and albumin were also reduced to normal physiological level. The reduced urinary protein and pH were also normalized. The serum urobilinogen, urea and total bilirubin levels were also reversed to normal levels while the diminished albumin and total protein levels also came to normal. The important phase I and II enzyme levels were also reversed in A. parviflora administered rats. The H2O2, thiobarbituric acid reactive substance (TBARS) and nitrite levels were significantly decreased. Furthermore, the damaged DNA and histopathological changes in CCl4 exposed rats were also highly significantly reversed after the administration of A. parviflora. All effects were significant (P < 0.05) and highly significant (P < 0.005) at 100 and 300 mg/kg respectively. Conclusion The restored urine and serum profile of various parameters to normal physiological levels suggests that the A. parviflora has potential antioxidant and repairing potential in renal disorders.